Acupuncture: A Review. Issue 4 (July 1996) - Hsu, Dora T.
Abstract : Background and Objectives: Acupuncture plays an important role in today's multidisciplinary approach to the treatment of pain. Its initial use, around the fifth century B.C., was based on the fundamentals of traditional Chinese medicine. Because of the lack of sound, supportive scientific data, the validity of such practice is controversial. Methods: A general review of this subject is presented including the history and classical theory behind acupuncture, needling techniques, precautions and complications, and types of acupuncture. Furthermore, in search of more scientific data, a review of several basic and clinical research articles was undertaken to evaluate a possible scientific basis for the mechanism of acupuncture analgesia. Problems and limitations of adequately designed dinical trials were also addressed. Results: Several lines of evidence support the endorphin-mediated mechanism of acupuncture analgesia. High- or low-frequency stimulation induced by electrical acupuncture has been shown to release different types of endorphins. To date, there are flaws in the conventional, scientific, clinical research methods applied to the evaluation of acupuncture practice for treatment of pain. Some guidelines and suggestions for future clinical trials are presented. Conclusion: Scientific data on acupuncture have been accumulating over the years, but further adequately designed clinical studies are necessary to provide additional validity for this treatment modality.